Perlindungan Hukum terhadap Sarjana Penggerak Pembangunan Indonesia (SPPI) atas Keterlambatan Pembayaran Gaji sebagai Kepala Satuan Pelayanan Pemenuhan Gizi (SPPG) di Kota Palangka Raya - Nurdiana; Novea Elysa Wardhani; Elin Sudiarti (Jurnal Hukum Lex Generalis, 2025)
The Sarjana Penggerak Pembangunan Indonesia (SPPI) Program deploys university graduates as Heads of the Nutrition Fulfillment Service Units (SPPG) to support the "Golden Indonesia 2045" vision. However, delays in salary payments have impacted their welfare and the quality of services provided. This empirical legal research conducted at the SPPG in Palangka Raya City indicates that these delays are caused by administrative factors, budgetary constraints, regulatory issues and coordination challenges. Legal protection for these graduates can be implemented through both preventive and repressive measures.